The complete chloroplast genome sequence of Patrinia monandra: a traditional Chinese medicinal herb - Xinhong Wang; Lulu Li; Xiaojun Ma; He Su; Jing Shu (Mitochondrial DNA. Part B. Resources, 2022)
Patrinia monandra C. B. Clarke is traditionally used for the treatment of inflammation, typhoid fever, injuries due to falls, abdominal pain, malaria, and acute appendicitis ulcers in China and Korea. In this study, the complete chloroplast genome of P. monandra was sequenced using the Illumina HiSeq X-Ten platform. It had a circular shape and a length of 158,940 bp, with 38.51% GC content. It contained a large single-copy region of 87,641 bp, a small single-copy region of 12,807 bp, and two inverted repeat regions of 29,246 bp. In total, 128 different genes, including 83 protein-coding genes, 37 distinct tRNA genes, and eight rRNA genes, were identified. Maximum-likelihood phylogenomic analysis showed that P. monandra is closely related to Patrinia scabiosifolia and Patrinia villosa in the Valerianaceae family. There were 4535 variable sites, 157,354 conserved sites, and 3085 singleton sites in the six Patrinia chloroplast genomes.